COSMOTHEANDRIC: HUBUNGAN ANTAR AGAMA MENURUT RAIMON PANIKKAR DAN RELEVANSINYA TERHADAP HUBUNGAN ANTAR AGAMA DI INDONESIA - Azis Pajri S. (UIN Sunan Kalijaga Yogyakarta, 2015)
Indonesia serves as a countr y with variety of cultures, traditions and religions. Religion, as one of the assets, becomes the problem in interfaith encounter when it faces the truth claim and ag gressive mission. As the consequence, the unexpected conflict happens that resulted in abundant victim and material loss. Two queries include Raimon Panikkar’s cosmotheandric concept in interfaith relation and its relevance on inter-religious relation in Indonesia. This article uses library research applying Peter L. Ber ger’s social construction theor y to analyze the construction of Panikkar’s concept and its relevance on inter-religious relation in Indonesia. Cosmotheandric, in this context, is a reality connected theos, anthropic and cosmos dimension. Panikkar’s Cosmotheandric has been constructed from Christian Trinity, Hinduism Advaita Vedanta and Buddhism Pratityasamut. Religion, in cosmotheandric structure, is situated in the antropical dimension. As the result, Panikar views religions as a part of reality that constructed Cosmotheandric reality. In this regard, religions bore the interconnected entity that constructed Cosmotheandric reality. The application of idea in Indonesian context is done by altering the Cosmotheandric language into local expressions that has sound meaning with theos, antropos and cosmos.